Hubungan Kebijakan Social Distanching Terhadap Kecemasan Ibu Dalam Pelaksanaan Rawat Gabung Bayi Selama Pandemi Covid-19 Di Klinik Henny Martubung Medan - Debi Novita Siregar; Khairani Sari; Feby Maidea Indah Astari; Irma Yunita Siregar (Elisabeth Health Jurnal, 2021)
Background: The Covid-19 pandemic has made the public, especially post partum mothers, anxious and limited in their activities due to the application of the principle of social distancing through the policy of Large-Scale Social Restrictions (PSBB). The purpose of this study was to determine the relationship between social distancing policies and maternal anxiety in implementing infant care during the Covid-19 pandemic Methods: This type of research is an analytic survey using a cross sectional design. The sample is post partum mothers who gave birth on November 1 to November 27, 2021 totaling 33 people. Data analysis using Chi Square. Results: The results of the study were obtained from 33 post partum mothers (100%), the majority felt anxious as many as 26 people (78.8%) and felt not anxious as many as 7 people (21.2%). It can be concluded that there is a relationship between social distancing policies and maternal anxiety in the implementation of babysitting during the Covid-19 pandemic Conclusion: attention from mothers as often as possible so that mothers also get experience in caring for babies while at the clinic, and mothers and babies get inner closeness